MODEL OF ASSIMILATION/INTEGRATION OF IMMIGRANTS - Shovkovyy, Oleg Cohan (PEOPLE: International Journal of Social Sciences, 2020)
The article aims to familiarize the scientific community with one of the results of a qualitative case study investigation that employed ethnographic methods of gathering data on Russian-speaking immigrants in the Brisbane region, Queensland, Australia, conducted in 2016-2017. The study, titled "Perceptions of Russian-speaking immigrants: A case study in Australia," was held in response to one of the most pressing and challenging questions on the agenda of many public administration offices around the world –"What can be done for better integration/assimilation of immigrants into host communities?" It set itself to identify factors affecting the processes of assimilation and integration of Russian-speaking immigrants into Australian society. The research not only pointed out alleged obstacles such as (1) employment, (2) education, (3) healthcare, (4) government assistance, and (5) discrimination but also suggested the theoretical Model of Assimilation/Integration of Immigrants (MAI). The proposed model could explain not only why immigrants cannot integrate easily into the host society but also some other futures of their behavior. The model indicates the possibility for quantification of assimilation/integration itself and thus, provides an opportunity for further comparison of degrees of assimilation in between population groups.